2010
DOI: 10.1177/0022022110363474
|View full text |Cite
|
Sign up to set email alerts
|

Harmony and Conflict: A Cross-Cultural Investigation in China and Australia

Abstract: Study 1 identified three distinct harmony factors in Hong Kong: disintegration avoidance, harmony enhancement, and harmony as hindrance. Furthermore, disintegration avoidance was found to relate positively to conflict avoidance and negatively to negotiation in a conflict situation. Study 2 examined how the harmony factors were related to various conflict styles in China and Australia. The three harmony factors were identifiable in Australia, but the Chinese scored higher in both disintegration avoidance and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
228
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(239 citation statements)
references
References 37 publications
11
228
0
Order By: Relevance
“…In contrast, people high on disintegration avoidance focus on the negative consequences of a strained relationship and avoid actions or events that may hurt interpersonal relationships to protect their self-interest. These two individual orientations have been validated in China and Australia (Leung et al, 2011), as well as in Singapore (Lim, 2009). Across these three cultural groups, harmony enhancement is related to the conflict style of integrating or problem solving, while disintegration avoidance, conflict avoidance.…”
mentioning
confidence: 99%
“…In contrast, people high on disintegration avoidance focus on the negative consequences of a strained relationship and avoid actions or events that may hurt interpersonal relationships to protect their self-interest. These two individual orientations have been validated in China and Australia (Leung et al, 2011), as well as in Singapore (Lim, 2009). Across these three cultural groups, harmony enhancement is related to the conflict style of integrating or problem solving, while disintegration avoidance, conflict avoidance.…”
mentioning
confidence: 99%
“…Relating cultural differences in dialectical reasoning to conflict, Leung, Brew, Zhang, and Zhang (2011) suggested that Chinese people perceive harmony as "a two-edged sword with both pros and cons." Moreover, research on culture and emotion has generally shown that, compared to their North American peers, East Asians (high dialectical thinkers) tend to be more comfortable with mixed emotions (e.g., Kitayama, Markus, & Kurokawa, 2000;Schimmack, Oishi, & Diener, 2002), that usually accompany conflict situations.…”
Section: Conflict Culture and Team Identitymentioning
confidence: 99%
“…To explore how cultural patterns are carried by social assumptions or norms, Kwok pioneered a model of the basic dimensions of social axioms (Leung & Bond, 2004). His works on fairness judgment and harmony offered exemplary illustrations of how emic and etic research programs inform and stimulate each other (Leung, Brew, Zhang, & Zhang, 2011;Morris, Leung, Ames, & Lickel, 1999). A culmination of this sustained inquiry came in a recent conceptual paper (Leung & Morris, in press) that integrated many of his insights by proposing the conditions, respectively, under which values, schemas, and norms operate: Values play a more important role in accounting for cultural differences in weak situations where fewer constraints are perceived; schemas play a more important role when situational cues increase their accessibility and relevance; and norms play a more important role when social evaluation is salient.…”
mentioning
confidence: 99%